Not just a game: Identity fusion and extremism in gaming cultures - Kowert, Rachel; Martel, Alexi; Swann, William B. (Frontiers in Communication, 2022)
Extremist ideologies have clearly become increasingly prevalent in the world of video games. What is less clear, however, is the mechanism through which these ideologies make their way into the psyches of gamers. Here we focus on the potential role of identity fusion in the radicalization of video gamers. In three studies, we show that fusion with gaming culture is uniquely predictive of a host of socially pernicious outcomes, including racism, sexism, and endorsement of extreme behaviors. We also show that specific personality attributes (e.g., insecure attachment, loneliness) may interact with fusion with gaming culture to further amplify support for extreme behavior, and that specific gaming communities (e.g., Call of Duty) may serve as catalysts that encourage strongly fused gamers to embrace antisocial attitudes and behaviors. These findings contribute to a theoretical understanding of the psychological processes that foment radicalization and guide the development of strategies for discouraging extremist ideologies in gaming spaces.